Effect of light quality on the growth and photosynthetic characteristics of Cinnamomum camphora rooted cuttings. Issue 7 (17th November 2021) - Zhou, Hua; Liu, Shujuan; Yang, Yanfang; Yang, Aihong; Liu, Lipan; Yu, Faxin
ABSTRACT: In order to improve Cinnamoum camphora seedling efficiency, we explored the effects of light quality in plant factories on the growth and photosynthetic characteristics of C. camphora . The results showed that four LED light quality treatments (red light, blue light, red light:blue light = 8:1, red light:blue light:UV-A = 20:5:1) all increased the plant height and leaf number of container seedlings of C. camphora compared to solar light under natural conditions. Under the blue light treatment, C. camphora stocks had the lowest biomass, including number of leaves, plant height, stem diameter, and fresh/dry weight. Under the red light treatment, stomatal conductance, intercellular CO2 concentration, transpiration rate, chlorophyll a, chlorophyll b and carotenoids were the lowest. Compared with the narrow-band red or blue light treatments, plant height, leaf number, fresh weight of aboveground biomass, fresh weight of belowground biomass and chlorophyll a content were significantly increased in both of the polychromatic light treatments. The polychromatic light treatment red light:blue light:UV-A = 20:5:1 significantly increased the net photosynthetic rate of C. camphora . Therefore, the polychromatic light treatment of red and blue light for C. camphora seedlings was better than narrow-band light treatments, and the addition of UV-A radiation was beneficial in cultivating strong seedlings.